2000
DOI: 10.1038/sj.bmt.1702508
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus infections following haematopoietic cell transplantation: is there a role for adoptive immunotherapy?

Abstract: Summary:Adenovirus has been recognised as an important pathogen in BMT recipients, especially in patients with GVHD and those receiving T cell-depleted allografts. We report adenovirus infections from an ongoing surveillance study in four patients after a non-myeloablative transplant and their improved outcome following withdrawal of immunosuppression in two patients and donor lymphocyte infusion for relapsed disease in the others. We discuss the control of adenovirus infections following immune manipulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 12 publications
2
62
1
Order By: Relevance
“…One key question to be answered in this setting is whether selected cells offer any real advantage over small doses of unselected donorlymphocytes. Although there is some concern about the possible risk of GvHD, successful application without this complication has been reported (Hromas et al, 1994;Chakrabarti et al, 2000b) and we have similar experience (unpublished observations). Expansion of BK virus-specific T cells is also possible using analogous strategies (Comoli et al, 2003;Blyth et al, 2011) and a number of groups are now evaluating their use, although their clinical experience is not yet published.…”
Section: Cellular Immunotherapysupporting
confidence: 55%
“…One key question to be answered in this setting is whether selected cells offer any real advantage over small doses of unselected donorlymphocytes. Although there is some concern about the possible risk of GvHD, successful application without this complication has been reported (Hromas et al, 1994;Chakrabarti et al, 2000b) and we have similar experience (unpublished observations). Expansion of BK virus-specific T cells is also possible using analogous strategies (Comoli et al, 2003;Blyth et al, 2011) and a number of groups are now evaluating their use, although their clinical experience is not yet published.…”
Section: Cellular Immunotherapysupporting
confidence: 55%
“…Interestingly, in one patient with viruria for 14 weeks, this cleared after DLI for relapsed leukaemia. 24 Lymphoproliferative responses to polyomaviruses has been demonstrated in post-BMT patients 25 and our observations seem to suggest that the virus is susceptible to cellular immunity.…”
Section: Discussionmentioning
confidence: 81%
“…19 HAdV secretion disappeared in four SCT recipients, who were treated for a leukaemia relapse after SCT either by tapering of ciclosporin A or by DLI infusion. 20 An additional study in a larger cohort of patients showed a strong association between immune reconstitution and elimination of HAdV infection. 21 Data obtained in ORD/MUD SCT recipients from our retrospective study indicated that patients with a low T-cell count (either CD4 þ or CD8 þ T cells) after SCT are at risk of developing an HAdV infection.…”
Section: Immunity and Hadv Infectionmentioning
confidence: 99%